The Influence of Designing Stickers as a Promoting Media for Ecotourism Mangrove Development in Bangkalan, Madura - Eri Zulkhaeriyah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This research aims to designing a media campaign especially a sticker as promoting media to develop ecotourism Mangrove in Bangkalan, Madura. Ecotourism Mangrove in Bangkalan is one of the sites that have potential in Madura. One of the Mangrove in Bangkalan is Labuhan has the potential of natural beauty and cultural wealth of high value in the market Ecotourism industry. The problem is less widely known by other tourist. In terms of promotion, this time Mangrove Labuhan only known by one person to others and carry out promotional activities in the form of banners. In addition, a website designed Mangrove Labuhan not much visited by visitors. So, information about Ecotourism Mangrove Labuhan is less known by the public. So from this problems takes some effort to influence people visit Ecotourism Mangrove, one of them is to design the appropriate media campaign for Ecotourism Mangrove Labuhan who can provide information to the public. The data collection method is documentation and observation with qualitative descriptive approach. Researchers collect data that is suitable for promotional media. In collecting data, the researchers use documentation data, after that processed in design with appropriate picture and language included in sticker. This research found that stickers have a significant influence in promoting mangrove ecotourism. Stickers can increase environmental awareness, tourism attractiveness, education, community engagement, and local income.